Hepatorenal Syndrome: Aetiology, Diagnosis, and Treatment. (12th January 2015) - Low, G.; Alexander, G. J. M.; Lomas, D. J.
Abstract : Acute renal impairment is common in patients with chronic liver disease, occurring in approximately 19% of hospitalised patients with cirrhosis. A variety of types of renal impairment are recognised. The most important of these is the hepatorenal syndrome, a functional renal impairment due to circulatory and neurohormonal abnormalities that underpin cirrhosis. It is one of the most severe complications of cirrhosis with survival often measured in weeks to months. A variety of treatment options exist with early diagnosis and appropriate treatment providing the best hope for cure. This paper provides a comprehensive and up-to-date review of hepatorenal syndrome and lays out the topic according to the following sections: pathophysiology, historical developments, diagnostic criteria and limitations, epidemiology, precipitating factors, predictors, clinical and laboratory findings, prognosis, treatment options, prophylaxis, and conclusion.